Tumor Burden and Immunotherapy: Impact on Immune Infiltration and Therapeutic Outcomes - Kim, Samuel I.; Cassella, Christopher R.; Byrne, Katelyn T. (Frontiers in Immunology, 2021)
Cancer immunotherapy has revolutionized the treatment landscape in medical oncology, but its efficacy has been variable across patients. Biomarkers to predict such differential response to immunotherapy include cytotoxic T lymphocyte infiltration, tumor mutational burden, and microsatellite instability. A growing number of studies also suggest that baseline tumor burden, or tumor size, predicts response to immunotherapy. In this review, we discuss the changes in immune profile and therapeutic responses that occur with increasing tumor size. We also overview therapeutic approaches to reduce tumor burden and favorably modulate the immune microenvironment of larger tumors.